Efektivitas Pemberian Air Jahe Merah Terhadap Penurunan Intensitas Nyeri Dismenorea Pada Remaja Putri - Putri Isti Karomah; Diah Atmarina Yuliani (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Dysmenorrhea results from an excessive amount of prostaglandins. The chemical content of gingerol in red ginger can block prostaglandins to reduce pain at the time of menstruation. Aims: To analyze the effectiveness of giving red ginger water in reducing the intensity of dysmenorrhea pain in young women. Metode: Quantitative research method- pre-experiment design, One Group Pretest Posttest Design. The sample uses a non-probability sampling technique with a purposive sampling method. The instrument uses a Numeric Rating Scale (NRS) questionnaire. Meanwhile, data analysis used the Wilcoxon test with a confidence level of α = 0.05. Results: Showed that there was effectiveness between red ginger water and dysmenorrhoea where p-value = 0.0001. Conclusion: There is effectiveness between red ginger water and dysmenorrhoea. It is suggested that the findings of this study can be a solution to overcoming dysmenorrhoea by using a type of non-pharmacological therapy, namely the administration of red ginger water.